REVIEWING THE ROLE OF INTRAVENOUS STEROIDS IN BLUNT CHEST TRAUMA-LUNG CONTUSION - KULKARNI, PRANAV CHANDRAKANT; HIREMATH, RAVISHEKAR N; GHODKE, SANDHYA; VERMA, VISHAL; MITTAL, MOHIT (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to see the effect of intravenous steroids in patients with blunt chest trauma-lung contusion and to compare the effect of steroid use based on improvement in oxygen saturation, ABG, and hospital stay, in the study group and control group. Methods: A prospective and observational study was carried out on patients with blunt chest trauma having lung contusion who were admitted to the multispecialty hospital for 2 years. Data were collected in a predesigned proforma. All patients with radiologically proven lung contusion were observed based on the steroid treatment given or not. Group A was steroid (study) group and Group B was non-steroid (control) group with 25 sample size in each group. Group A patients were treated with steroid (hydrocortisone) 20 mg/kg/day 6 hourly which was tapered over time. Control group patients were treated identically except for steroid use. Results: Most of the injuries affected the middle age group (25 to 65 years) which accounted for a total of 84%. The percentage of males and females in the study were 76% and 24%, respectively. The most common mode of injury was road traffic accidents which account for 76% as compared to non-road traffic accidents (24%). Statistical analysis showed there was an improvement in both groups in parameters such as Spo2, ABG-Pco2, and ABG-Sao2 and were statistically significant. While other improvements like ABG-Po2, radiological CT, and hospital stays were statistically insignificant. Conclusions: As both groups were showing improvements and there was no statistically much difference seen in both groups, we concluded that there is no role of intra-venous steroid use in lung contusion. However, every patient must undergo CT for a better assessment of the injury. Objective scoring systems are required in CT assessment of lung injury and studies with increased sample size and carried out at multiple centers are required for better conclusions.